Five-Year Occupational Radiation Exposure of Nuclear Medicine Personnel: Whole-Body, Skin, Estimated Eye Lens, and Extremity Dosimetry in Southwestern Hospital of Saudi Arabia - Mohammed A. Jowhari; Sarah M. Al-Mamar; Anwar I. Al-Qaflah; Nouf K. Al-Mazmumi; Al-Hanouf A. Al-Rasasmeh; Saeed Mueed Al-Qahtani; Mohammad Sayed; Ismail M. Moafa; Mansour M. Alqahtani (Applied Sciences, 2026)
Occupational radiation exposure in nuclear medicine (NM) is heterogeneous because personnel handle unsealed radionuclides and work near injected patients. This five-year retrospective study characterised whole-body Hp(10), whole-body Hp(0.07), ring Hp(0.07), and estimated eye-lens Hp(3) in six NM staff over 20 quarterly monitoring cycles (2020–2024). TLD-100 whole-body and ring dosimeters were analysed, and Hp(3) was estimated from collar-level Hp(0.07), with two alternative surrogates examined in sensitivity analyses. Temporal trends were assessed using mixed-effects models supported by worker-cluster bootstrap, log-transformed, Winsorised, and Benjamini–Hochberg-adjusted analyses. A total of 120 quarterly measurements per quantity were available. Mean annual doses were 1.3 ± 0.44 mSv for Hp(10), 1.4 ± 0.37 mSv for Hp(0.07), 1.4 ± 0.37 mSv for estimated Hp(3), and 4.3 ± 3.8 mSv for ring Hp(0.07). All doses remained well below ICRP limits. Ring dose showed a robust downward trend across sensitivity analyses, whereas the Hp(10) decline was directionally suggestive but statistically fragile under small-cluster inference; Hp(0.07) remained stationary. The low ring-to-Hp(10) ratio and low estimated Hp(3) values support continued ALARA optimisation, while the observed inter-individual variability identifies extremity handling as a priority for future monitoring.